The Meaning of Sunnah and Bid'ah in an Islamic Perspective - Syukur, Syukur; Huda, Miftahul (Green Publisher Indonesia, 2025)
This study explores the concepts of Sunnah and Bid'ah in Islamic thought, highlighting their theological significance and practical implications in Muslim life. The Sunnah encompasses the sayings, actions, and tacit approvals of the Prophet Muhammad PBUH, serving as a complementary guide to the Qur'an in matters of worship, daily conduct, and social interactions. Conversely, Bid'ah refers to innovations in religious practices that lack a foundational basis in the Qur'an or Sunnah. This paper aims to provide a nuanced understanding of Bid'ah, including its classifications—Bid'ah Hasanah (commendable innovation) and Bid'ah Sayyiah (blameworthy innovation)—as interpreted by classical and contemporary Islamic scholars. Using a qualitative descriptive approach through literature review and textual analysis of Islamic sources, this research critically examines the perspectives on the permissibility and consequences of religious innovations in domains such as worship, education, and governance. The findings suggest that while innovation in secular matters may be acceptable, innovation in ritual worship requires scrutiny. The paper underscores the necessity of preserving the integrity of Islamic teachings by adhering to the Prophet’s traditions and being cautious of unauthorized religious practices. This study contributes to the discourse on Islamic jurisprudence by reinforcing the balance between tradition and contextual understanding in addressing contemporary challenges.